Milk flow pattern, somatic cell count and teat apex score in primiparous dairy cows at the beginning of lactation - Zucali, Maddalena; Bava, Luciana; Sandrucci, Anna; Tamburini, Alberto; Piccinini, Renata; Daprà, Valentina; Tonni, Mirella; Zecconi, Alfonso (Italian journal of animal science, 2009)
The aim of the study was to investigate the relationships between milk flow traits, milk Somatic Cell Count (SCC) and teat apex score in primiparous cows during the first 120 days of lactation. A total of 82 primiparous Holstein cows were randomly selected in 6 herds characterized by different milking machines and management. The cows were monitored monthly during the first 120 days of lactation. Each month, milk flow curves of the whole udder of each primiparous cow were registered with continuous electronic milk flow meters (Lactocorder), quarter milk samples were aseptically collected, somatic cells were counted, and teat apex scores were assessed. Quarter milk samples were divided in two groups according to SCC: <200,000 and >200,000 cells/ml, respectively. At udder level each cow was classified as low SCC (LSCC) when all quarters had <200,000 cells/ml and high SCC (HSCC) in all other situations, separately for each control. Animals with at least one HSCC control during the first 120 days of lactation (n=33), compared to subjects always classified as LSCC cows (n=49), showed significantly higher average milk flow (2.32 vs 2.13 kg/min; P<0.05), peak milk flow (3.71 vs 3.14 kg/min; P<0.05), lower duration of plateau phase (2.33 vs 3.27 min; P<0.05), longer duration of increase phase (0.81 vs 0.66 min; P<0.05), and higher average SCC (4.07 vs 3.45 Log 10 SCC; P<0.05). Moreover, primiparous cows with at least one HSCC control had a significant increase in peak milk flow during the first four months of lactation, while the other cows showed only a slight increase. Teat apex scores significantly increased in both groups of primiparous cows as lactation progressed but values in subjects always classified as LSCC animals were constantly lower with respect to cows with at least one HSCC control. The results obtained in this study support the relationship between SCC, teat apex score and milk flow traits.